3-month versus 6-month adjuvant chemotherapy for patients with high-risk stage II and III colorectal cancer : 3-year follow-up of the SCOT non-inferiority RCT.: 3-year follow-up of the SCOT non-inferiority RCT. (2019) - Unknown
No abstract available